CONTROL FUNCTION OF LEGISLATIVE POWER:QUESTIONS OF THEORY AND PRACTICE (Journal of actual problems of jurisprudence, 2019)
In given article conceptual positions of the theory of the parliamentary control from the point of view of division of the authorities are considered, its specific lines as process, as certain kind of administrative activity are revealed.